2012
DOI: 10.1111/j.1365-2036.2011.04977.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sildenafil on rectal sensitivity and tone in patients with the irritable bowel syndrome

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The findings suggested that various herbal remedies, such as passionflower, may play some role in the alleviation of anxiety [124]. Some target synthetic compounds focusing on depression and anxiety, such as phosphodiesterase 5 inhibitors, have also been proven to be effective in neutralizing radical oxygen species, which may result in the treatment of anxiety-related disorders, such as the irritable bowel syndrome [125]. …”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that various herbal remedies, such as passionflower, may play some role in the alleviation of anxiety [124]. Some target synthetic compounds focusing on depression and anxiety, such as phosphodiesterase 5 inhibitors, have also been proven to be effective in neutralizing radical oxygen species, which may result in the treatment of anxiety-related disorders, such as the irritable bowel syndrome [125]. …”
Section: Introductionmentioning
confidence: 99%
“…As a group, patients with IBS report higher levels of anxiety and depression (Goncalves de Medeiros et al, 2012; Jones, Koloski, Boyce, & Talley, 2011; Orr, Crowell, Lin, Harnish, & Chen, 1997), stress and more co-morbid conditions (Gulewitsch, Enck, Hautzinger, & Schlarb, 2011) suggesting that CPM efficiency may be reduced. In addition, several studies found that IBS patients have dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis as evidenced by either hyper or hyposecretion of cortisol or dysregulation between ACTH and cortisol levels (Chang et al, 2009; Heitkemper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of six studies were included. 15,17,18,37,38,65 In those studies, healthy-control groups were used for multiple comparisons with the three IBS-subtypes; we divided the healthy-control group into three groups for meta-analysis of three IBS-subtypes alongside healthy controls. Depression levels were significantly higher in IBS-C (SMD = 0.83; 95% CI, 0.61-1.06; I 2 = 0%; P < 0.001), IBS-D (SMD = 0.73; 95% CI, 0.51-0.96; I 2 = 0%; P < 0.001), and IBS with mixed bowel habits (SMD = 0.62; 95% CI, 0.39-0.84; I 2 = 0%; P < 0.001) (Fig.…”
Section: Depression and Anxiety In Irritable Bowel Syndrome-subtypementioning
confidence: 99%